2021
DOI: 10.15562/bmj.v10i2.2340
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of mandibular fractures in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia

Abstract: Background: Mandibular fractures may lead to several complications, including infection, nonunion, malunion, and temporomandibular joint ankylosis. The incidence of mandibular fractures is quite common in maxillofacial trauma. The characteristics of mandible fractures could be different among countries concerning the condition of the population. The etiological differences depend on age, demographic patterns of a country, environmental conditions, social conditions, socioeconomic status and cultural configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Therefore, they require immediate treatment to reduce severe pain and infection, and to stop ongoing tissue bleeding. 19 Strongly influences oro-maxillofacial trauma care activities. 20 The authors found that the number of oro-maxillofacial trauma patients was inversely related to the evolution of the COVID-19 pandemic, with significantly fewer patients accessing hospital emergency rooms for dental care during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, they require immediate treatment to reduce severe pain and infection, and to stop ongoing tissue bleeding. 19 Strongly influences oro-maxillofacial trauma care activities. 20 The authors found that the number of oro-maxillofacial trauma patients was inversely related to the evolution of the COVID-19 pandemic, with significantly fewer patients accessing hospital emergency rooms for dental care during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…20 The authors found that the number of oro-maxillofacial trauma patients was inversely related to the evolution of the COVID-19 pandemic, with significantly fewer patients accessing hospital emergency rooms for dental care during the pandemic. 14,15,18,19 In times of the COVID-19 pandemic, with fewer available inpatient beds, data can be helpful for predicting the need for non-delayed hospital care for oral and maxillofacial surgery, and for managing hospital organizations to respond to reductions in surgical options; this was also reported in most countries in comparison to emergency procedures. 13,14,15 A medical literature shows how the pandemic outbreak had also caused patients to leave the hospital, possibly due to the fear of SARS-CoV-2 contact.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations